2018
DOI: 10.1021/acs.jpcc.8b06748
|View full text |Cite
|
Sign up to set email alerts
|

Role of ReOx Species in Ni-Re/Al2O3 Catalyst for Amination of Monoethanolamine

Abstract: The role of ReO x species in Ni-Re/Al 2 O 3 catalyst for amination of monoethanolamine (MEA) was investigated using a combination of experimental (Raman spectroscopy, in situ X-ray photoelectron spectroscopy, transmission electron microscopy, X-ray diffraction, scanning transmission electron microscopy−energydispersive X-ray spectroscopy line scan, and extended X-ray absorption fine structure) and theoretical (density functional theory (DFT)) methods. Characterization and simulation results indicate that rheni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 72 publications
3
25
0
Order By: Relevance
“…As shown, the two samples exhibited similar Ni 2p spectra. Besides a binding energy at approximately 862.5 eV assigned to the shake-up satellite of Ni 2p3/2, two peaks at approximately 853.0 and approximately 856.0 eV were observed, which were ascribed to Ni 0 and NiO species [38,44], respectively. Moreover, it was observed that the binding energy of Ni 0 species shifted from 853.5 eV for Ni/AC to a higher binding energy of 854.0 eV for Ni-Re/AC(n Ni :n Re = 1:1).…”
Section: Xps Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown, the two samples exhibited similar Ni 2p spectra. Besides a binding energy at approximately 862.5 eV assigned to the shake-up satellite of Ni 2p3/2, two peaks at approximately 853.0 and approximately 856.0 eV were observed, which were ascribed to Ni 0 and NiO species [38,44], respectively. Moreover, it was observed that the binding energy of Ni 0 species shifted from 853.5 eV for Ni/AC to a higher binding energy of 854.0 eV for Ni-Re/AC(n Ni :n Re = 1:1).…”
Section: Xps Resultsmentioning
confidence: 99%
“…Nanomaterials 2020, 10, x FOR PEER REVIEW 8 of 14 Figure 5 presents the XPS spectra of the Re 4f region for Re/AC and Ni-Re/AC(n Ni :n Re = 1:1). For the two samples, five deconvoluted peaks appeared at 40.8, 41.9, 43.2, 45.0, and 45.8 eV, which were assigned to the 4f7/2 of Re 0 , Re 3+ , Re 4+ , Re 6+ , and Re 7+ species [38,44], respectively. Similar phenomena for Re 4f spectra were also found for other Ni-Re samples (See Figure S3 in the Supplementary Material).…”
Section: Xps Resultsmentioning
confidence: 99%
“…Ayvali et al found that dissociation of CO at the metallic surface of small RuRe NPs was easier than with pure Ru and Re (as the result of a synergic effect) and therefore, high reactivity towards CO dissociation validates the use of bimetallic structures in the Fischer-Tropsch process [18]. The recently reported studies for Re-based bimetallic catalysts, for example for the Re-Ni/ Al 2 O 3 catalysts, indicate that Re promoter could effectively suppress the Ni 0 sintering process [19]. Also, for the bimetallic Co-Re particles supported on Al 2 O 3 superior sintering resistance was reported by Mom et al [20].…”
Section: Introductionmentioning
confidence: 74%
“…It is also possible that part of rhenium species is associated with the ruthenium phase, and there was an enrichment of ReO x species at the peripheral interface of the RuO 2 particles and the γ-Al 2 O 3 and additionally, some rhenium species may also exist as a thin film on top of the RuO 2 oxide particles. Ma et al[19] studied the role of ReO x species in the Ni-Re/Al 2 O 3 catalyst for amination reaction using a combination of various experimental and theoretical methods and found that rhenium oxide species prefer to atomically disperse on the surface of NiO in calcined Ni-Re/ Al 2 O 3 catalyst. Our XRD results clearly show that metal segregation in the bimetallic Ru-Re catalysts leads to RuO 2 agglomeration and transformation of the Re phase into a highly dispersed species.…”
mentioning
confidence: 99%
“…The catalytic performance of the Ni-Re/SiO2 catalysts for MEA amination was evaluated in a trickle-bed reactor. As described previously [21,22], about 3.6 ml (1.9 g) of oxide state catalysts were placed in the center of a stainless steel reaction tube, and the residual space was filled with silica sand. Before reaction, the catalyst was reduced in situ.…”
Section: Activity Measurementsmentioning
confidence: 99%